2016
DOI: 10.1007/s10266-015-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to skeletal muscle mass in the frail elderly

Abstract: It is important for the elderly to maintain their skeletal muscle mass, which in turn helps to maintain physical functions. This study aimed to clarify factors related to skeletal muscle mass maintenance. Home-bound elderly (94 men and 216 women), at least 75 years of age, attending a day-care center in Tokyo, were enrolled in this study. Dentists specializing in dysphagia rehabilitation evaluated skeletal muscle mass, occlusal status and swallowing function. Physical function, cognitive function and nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Dentists with expertise in dysphagia, in the city of Tokyo, assessed a group of older persons regarding their deglutition function, the occlusal function and the orofacial muscle mass, and their findings indicate that dental treatments and prosthesis-based rehabilitation are important resources for muscular maintenance, favouring the deglutition and nutrition of these older individuals. 26 As our study, another factor associated with deglutition, in the literature, is the Xerostomia. A study with individuals with Sjögren's syndrome shows that 32-85% of them report difficulty in deglutition due to the perception of reduced saliva.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Dentists with expertise in dysphagia, in the city of Tokyo, assessed a group of older persons regarding their deglutition function, the occlusal function and the orofacial muscle mass, and their findings indicate that dental treatments and prosthesis-based rehabilitation are important resources for muscular maintenance, favouring the deglutition and nutrition of these older individuals. 26 As our study, another factor associated with deglutition, in the literature, is the Xerostomia. A study with individuals with Sjögren's syndrome shows that 32-85% of them report difficulty in deglutition due to the perception of reduced saliva.…”
Section: Discussionmentioning
confidence: 55%
“…This condition, which includes a reduction in the number of teeth, malnutrition and dysphagia seem to prompt a vicious cycle. Dentists with expertise in dysphagia, in the city of Tokyo, assessed a group of older persons regarding their deglutition function, the occlusal function and the orofacial muscle mass, and their findings indicate that dental treatments and prosthesis‐based rehabilitation are important resources for muscular maintenance, favouring the deglutition and nutrition of these older individuals …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, whole‐body muscle mass loss has been shown to be related to swallowing function and chewing ability in older individuals. Furthermore, a significant decrease in skeletal muscle mass was found among frail older male patients who had no normal occlusion of their own teeth . Sarcopenia has been reported as an independent risk factor for dysphagia in hospitalized older people .…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
“…Furthermore, a significant decrease in skeletal muscle mass was found among frail older male Dysphagia due to sarcopenia © 2019 The Authors Geriatrics & Gerontology International published by John Wiley & Sons Australia, Ltd on behalf of Japan Geriatrics Society | patients who had no normal occlusion of their own teeth. 57 Sarcopenia has been reported as an independent risk factor for dysphagia in hospitalized older people. 58 Additionally, texture-modified diets have been associated with decreased whole-body skeletal muscle mass as measured by dual-energy X-ray absorptiometry in older adults admitted to a rehabilitation ward.…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
“…The main result of this study showed that the orofacial skeletal muscle mass was associated with the nutritional state. The findings showed that dental treatments and the use of dentures are important to keep the skeletal muscle mass, favoring swallowing and thus the older person's nutrition (Sagawa, Kikutani, Tamura, & Yoshida, ). The results, in addition, to confirm the importance of providing dental care support to the older persons with dysphagia, showed the importance of teeth support or dentures to keep proper orofacial motor skills.…”
Section: Discussionmentioning
confidence: 99%